Continuous 2000 K droplet-to-particle synthesis. (May 2020) - Wang, Xizheng; Huang, Zhennan; Yao, Yonggang; Qiao, Haiyu; Zhong, Geng; Pei, Yong; Zheng, Chaolun; Kline, Dylan; Xia, Qinqin; Lin, Zhiwei; Dai, Jiaqi; Zachariah, Michael R.; et al.
Graphical abstract: Abstract: Aerosol spray coupled with high-temperature pyrolysis is an emerging technique for continuous manufacturing of nanomaterials at large scale that demonstrates extremely high production efficiency. Current aerosol spray techniques using a tube furnace can only attain a low temperature range (generally <1500 K), rendering limited products as well as inhomogeneous heating within the comparatively bulky furnace chamber (typical dimensions of ≥2 cm in diameter and ≥40 cm in length), which leads to difficulties in product quality control. Here we report a "droplet-to-particle" aerosol technique coupled with a high-temperature (∼2000 K) micro-channel reactor, which provides ∼100-times smaller dimensions compared to conventional tube furnaces, enabling homogeneous and high-temperature nanomaterial manufacturing. To demonstrate the unique capability of this carbonized wood micro-channel reactor, we successfully synthesized multielement high entropy alloy/oxide nanoparticles (which typically require a high temperature (2000 K) to achieve uniform elemental mixing) in a continuous and support-free manner. Droplets atomized from the multielement precursors fly through the micro-channels heated to 2000 K by Joule heating with a residence time of only tens of milliseconds with a high energy conversion efficiency (>95%), during which salt decomposition and particle nucleation/growth occur. The high temperature critically enables homogeneous mixing of elements in the resultant nanoparticles and the short residence time is key to suppress particle growth and agglomeration. Compared with the traditional aerosol spray pyrolysis, the carbonized wood reactor can achieve a record high temperature (≥2000 K), a much shorter residence time (∼tens of milliseconds), highly efficient, uniform heating, and provide a platform for continuous nanomaterial manufacturing for a broad range of applications.